ANALISIS PENYEBAB BANJIR DI DKI JAKARTA - Eldi Eldi (Sekolah Tinggi Pariwisata Mataram, 2020)
The aim in this article is to find out various factors that caused floods occur in DKI Jakarta. The Research method in this article is used a descriptive research design using a literature study approach. Based on the type of research and data source is used, the data collection technique in this study is to used secondary data. Then the results of this research that have been carried out are that the causes of flooding in DKI Jakarta in general are due to dynamics and urban development, in which there are various aspects that can be seen, such as the demographic aspects of the city that lead to rapid population growth of an urban area and it causes various problems that occur in urban areas, the next aspects is land use, where the development of an urban area causes needed for land to be used as a residence in urban areas continues to experience enhancement. And the last aspect is land use change, which is where changes in land used patterns occur in urban areas from non-developed areas to built up areas that are related to the expansion of urban areas as physical manifestation and pressure due to urbanization.